Guanine: A Combined Study Using Vibrational Spectroscopy and Theoretical Methods. Issue 5 (11th July 2012) - Lopes Lopes, R. Pedro R. Pedro; Marques Marques, M. Paula M. M. Paula M.; Valero Valero, Rosendo Rosendo; Tomkinson Tomkinson, John John; de Carvalho de Carvalho, Luís A. E. Batista Luís A. E. Batista
Abstract : The present paper reports a conformational study of solid-state anhydrous guanine, using vibrational spectroscopy techniques—infrared, Raman, and inelastic neutron scattering—coupled to quantum mechanical methods at the DFT level, both for the isolated molecule and the condensed state. In both cases, the 7H-keto-amino tautomer was found to be the prevalent form, contrary to aqueous solutions and hydrated polycrystalline guanine, where the 9H-keto-amino tautomer is the most favoured species. This paper is a significant contribution for the existing spectroscopic characterization of this purine base, by unambiguously assigning its vibrational spectra.